Lenin. - Lih, Lars T. (Reaktion Books, 2012)
After Karl Marx, Vladimir Lenin (1870-1924) is the man most associated with communism and its influence and reach around the world. Lenin was the leader of the communist Bolshevik party during the October 1917 revolution in Russia, and he subsequently headed the Soviet state until 1924, bringing stability to the region and establishing a socialist economic and political system. In Lenin, Lars T. Lih presents a striking new interpretation of Lenin's political beliefs and strategies. Until now, Lenin has been portrayed as a pessimist with a dismissive view of the revolutionary potential of the.